An essay on conceptualization of issues in empirical accounting research - Bin N. Srinidhi (China Journal of Accounting Research, 2013)
Empirical research in accounting has lately focused much on sophisticated statistical methodology and econometrics and relatively less on conceptualization of the issues concerned. This essay is written to highlight the conceptualization of the issues as an important ingredient of empirical research in accounting. I present two methods of conceptualization - the single-entity approach and the game theoretic approach. I give several examples in accounting research to explain the conceptualization process. I hope that this essay will fill a much needed void in the research process in accounting and restore the balance between conceptualization and methodology.
Keywords: 650; Conceptualization; Maintained hypothesis; Single-entity approach; Game theory approach